The effect of compressed air massage on untraumatised rabbit skeletal muscle - a morphometric and ultrastructural study - M. A. Gregory; M. Mars (AOSIS, 2004)
One of the therapeutic uses of massage is to facilitate repair of damaged tissue. A potential hazard of massage is that direct pressure on muscle is known to damage skeletal myofibres. This study examines the effect of a new form of massage using compressed air on the morphology of untraumatised rabbit skeletal myofibres. Under anaesthetic, the left and right vastus lateralis muscles of 16 New Zealand, white rabbits were treated with 10 minutes of compressed air therapy at 1 Bar using a single hole (5 mm) applicator head and control biopsies were taken from the opposite limb. Biopsies were prepared for light microscopy and transmission electron microscopy. Morphometry, using image analysis revealed a significant increase in myofibre diameters 10 minutes  (p < 0.001) and 24 hours (p<0.01) after compressed air massage. Six days after treatment diameters were significantly reduced (p < 0.01). Morphologically, myofibres in control specimens were normal. Shortly after compressed air  massage, juxta-nuclear and intermyofibrillar oedema was present and electron-lucent spaces were filled with swollen mitochondria and elements of the sarcoplasmic reticulum (SR). Glycogen and other non-contractile organelles were sometimes aggregated in oedematous, sub-sarcolemmal regions. Twenty four hours after treatment, intermyofibrillar oedema was reduced, but SR swelling remained and many fibres were characterised by focal and large areas of myofibrillar disorganisation. With the exception of occasional swollen elements of the SR and a single internalised nucleus, myofibres morphology had returned to normal 6 days after treatment. Compressed air massage causes less damage to skeletal myofibres than a similar form of localised pressure treatment, deep transverse frictions. Clinical studies using this new modality are warranted.